Cost of multiple sclerosis in the Czech Republic: the COMS study - Blahova Dusankova, J; Kalincik, T; Dolezal, T; Kobelt, G; Havrdova, E (Multiple sclerosis (Houndmills, Basingstoke, England), 2012)
BACKGROUND: Information about cost of multiple sclerosis (MS) is available from a number of European countries, but no data from the Czech Republic have been published so far. OBJECTIVE: The objective of this study was to establish the cost of MS in the Czech Republic, overall and by level of disease severity. METHODS: Data on demographics, disease history, resource consumption and production losses were collected from 909 patients recruited in 7 MS centres in the Czech Republic. Annual costs were estimated in the societal perspective, using 2007 unit costs. To evaluate the relationship between disability and costs, patients were stratified into those with mild (67%), moderate (27%) and severe (10%) disability using the Expanded Disability Status Scale. RESULTS: Mean total annual costs per patient were €12,272, of which 51% were direct medical costs, 4% direct non-medical costs and 45% indirect costs. The average annual costs in patients with mild, moderate and severe disability amounted to €9905, €14,064 and €22,880, respectively. CONCLUSION: The total costs of MS in the Czech Republic are estimated at €208.6 million per year. Consistent with other studies, the costs increase significantly with the severity of MS.
Keywords: pracovní neschopnost; Disability Evaluation; Chi-Square Distribution; Analysis of Variance; absentérství; Male; retrospektivní studie; Sick Leave; pomůcky pro sebeobsluhu; Self-Help Devices; Multiple Sclerosis; posuzování pracovní neschopnosti; ambulantní péče; Česká republika; prognóza; Ambulatory Care; rozdělení chí kvadrát; náklady na zdravotní péči; prevalence; Adult; Home Care Services; návštěvy v ordinaci; dospělí; Cost of Illness; mužské pohlaví; Prospective Studies; Hospital Costs; Models, Economic; Employment; Income; Severity of Illness Index; nemocnice - náklady; služby domácí péče; Absenteeism; náklady na léky; Czech Republic; Time Factors; lidé; ekonomické modely; důchody; ženské pohlaví; analýza rozptylu; příjem; Humans; Health Care Costs; časové faktory; Prevalence; Pensions; Prognosis; zaměstnanost; Office Visits; stupeň závažnosti nemoci; Retrospective Studies; Female; lidé středního věku; roztroušená skleróza; osobní újma zaviněná nemocí; Drug Costs; Middle Aged; prospektivní studie